2011
DOI: 10.1016/j.bpg.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention in familial adenomatous polyposis

Abstract: Familial adenomatous polyposis (FAP) predictably leads to adenomas and eventual adenocarcinomas in the lower gastrointestinal tract and less frequently, the upper gastrointestinal tract. Chemopreventive strategies have been studied in FAP patients to delay the development of adenomas in the upper and lower gastrointestinal tract, as well as to prevent recurrence of adenomas in the retained rectum of patients after prophylactic surgery with colectomy and ileorectal anastamosis (IRA). The nonsteroidal anti-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 91 publications
3
60
0
2
Order By: Relevance
“…At present, no optimal adjuvant chemotherapy exists for clinical use; therefore, developing rationally designed, novel adjuvant therapeutic tools for the treatment of colon cancer is a constant requirement (2). Previously, the use of natural substances, including curcumin, eicosapentaenoic acid, apple polyphenols, capsaicin and thymoquinone (TQ), for cancer chemoprevention has been investigated (3)(4)(5). TQ is the primary active ingredient of volatile Nigella sativa (black cumin) seed oil, which is used as a spice in countries with a low incidence of colorectal cancer, including Egypt, Pakistan and India (6).…”
Section: Introductionmentioning
confidence: 99%
“…At present, no optimal adjuvant chemotherapy exists for clinical use; therefore, developing rationally designed, novel adjuvant therapeutic tools for the treatment of colon cancer is a constant requirement (2). Previously, the use of natural substances, including curcumin, eicosapentaenoic acid, apple polyphenols, capsaicin and thymoquinone (TQ), for cancer chemoprevention has been investigated (3)(4)(5). TQ is the primary active ingredient of volatile Nigella sativa (black cumin) seed oil, which is used as a spice in countries with a low incidence of colorectal cancer, including Egypt, Pakistan and India (6).…”
Section: Introductionmentioning
confidence: 99%
“…Colectomy should be considered when the patient presents with more than 20 adenomas, with the diameter of the adenoma exceeding 1cm or advanced histology findings (Jasperson et al, 2010). Chemoprevention with medications such as nonsteroidal anti-inflammatory drugs (NSAID) and selective cyclooxygenase-2 (COX-2) inhibitors delay the development of adenomas and prevent recurrence of adenomas in the retained rectum after prophylactic surgery (Kim and Giardiello, 2011). Long term adverse effects of these medications limit their use as medication chemoprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins have been postulated in having a role in altering cell adhesion, inhibiting apoptosis and promoting angiogenesis [ 109 , 110 ], all important components that are implicated in transforming tumors from benign to malignant lesions. Subsequent studies have suggested that NSAIDS exert most of their antineoplastic effects via the inhibition of the COX-2 enzyme and inhibition of other biochemical pathways independent of COX suppression [ 111 ].…”
Section: Chemopreventionmentioning
confidence: 99%